2018
DOI: 10.1038/s41420-018-0090-1
|View full text |Cite|
|
Sign up to set email alerts
|

DHA and 19,20-EDP induce lysosomal-proteolytic-dependent cytotoxicity through de novo ceramide production in H9c2 cells with a glycolytic profile

Abstract: Docosahexaenoic acid (DHA) and their CYP-derived metabolites, epoxydocosapentaenoic acids (EDPs), are important fatty acids obtained from dietary sources. While it is known that they have significant biological effects, which can differ between cell type and disease state, our understanding of how they work remains limited. Previously, we demonstrated that DHA and 19,20-EDP triggered pronounced cytotoxicity in H9c2 cells correlating with increased ceramide production. In this study, we examine whether DHA- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is also possible that a decrease in SCD1 may be associated with CYP1A1. One study of CYP1A1 (−/−) mice demonstrated that elevated expression of Cyp1a1 protects against NAFLD development, while dysregulation of the Cyp1a1 gene is reportedly involved in the transport and metabolism of lipids [ 28 , 29 ]. Transcription factor SREBP1, one of the master regulators of hepatic lipogenesis, can aggravate hepatic steatosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that a decrease in SCD1 may be associated with CYP1A1. One study of CYP1A1 (−/−) mice demonstrated that elevated expression of Cyp1a1 protects against NAFLD development, while dysregulation of the Cyp1a1 gene is reportedly involved in the transport and metabolism of lipids [ 28 , 29 ]. Transcription factor SREBP1, one of the master regulators of hepatic lipogenesis, can aggravate hepatic steatosis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent results obtained using CYP1A1(-/-) mice demonstrate that elevated expression of CYP1A1 protects against the development of non-alcoholic fatty liver disease [27], and dysregulation of the CYP1A1 gene is reported to be involved in the transport and metabolism of lipids [28].…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular fractions isolated from hearts were subjected to western blot analysis as previously described (Darwesh et al, 2018; Endo et al, 2018). Briefly, 25 μg of protein from heart tissues was resolved on a 12% SDS-polyacrylamide gel and transferred to polyvinylidene difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%